Physicochemical, microbiological, and sensory characterization of fresh cheese made with the Amazonian plants Mansoa alliacea and Eryngium foetidum in Pastaza, Ecuador - Ulloa, Janeth; Pérez , Manuel; Ettiene, Gretty; Briñez, Wilfido (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Plants have nutritional properties and beneficial effects on health, so fortifying dairy foods with plants from the Ecuadorian Amazon could produce dairy products with high nutritional values and unique aromas and flavors. This study characterized the physicochemical, sensory, and microbiological properties of fresh cheese made from the Amazonian plants: wild garlic (Mansoa alliacea; (Lam.) A.H.Gentr) and culantro (Eryngium foetidum L.). Cheeses were made with both species (dry sample and ethanolic extract) at 5 % and 25 % under a completely randomized experimental design with a 23 factorial arrangement, with three replications and 24 experimental units. The physicochemical properties established in the NTE INEN 1528 Standard (moisture, ash, dry matter, protein, fat, pH, acidity, lactose content, lactic acid, and chloride) were determined in the cheeses. Sensory analysis was performed with an untrained panel. Microbiological quality was assessed in the cheese selected in the preference test, according to the NTE INEN 1528 Standard. The treatments affected ash content (3.20 %), pH (5.95), moisture (55.28 %), total solids (42.20 %), and protein (20.84 %). The cheeses QF7 (dry extract of culantro, 5 %) and QF3 (dry extract of wild garlic, 5 %) presented the highest median acceptance, corresponding to "I like it very much", with QF7 getting the highest acceptance (71 %). The fresh cheese presented high protein, fat, and calcium content, as well as adequate microbiological quality, which characterizes it as a caloric and nutritional food.